The Implications of Abraham Lincoln's Emancipation Proclamation on the Education of Enslaved People in America - Yusuf, Rusydi M. (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This paper discusses how Abraham Lincoln's Emancipation Proclamation had an extraordinary impact on the development of education for enslaved people, particularly African Americans, after the Civil War. It also highlights how the long-standing practice of slavery in America, which had persisted for centuries, was boldly challenged by Lincoln's declaration to abolish it. Lincoln issued a policy to eliminate slavery, which significantly influenced their level of education in the years that followed. This paper used a qualitative method with a historical approach to explain the social aspects of life in the past. The research findings indicate that during the era of slavery, enslaved individuals were heavily bound by various rules imposed by plantation owners. These rules had to be obeyed without any means of self-defense. Enslaved people were considered property of landowners, who could sell them and treat them as they pleased. Abraham Lincoln sought to abolish this practice by issuing a presidential decree in the form of the Emancipation Proclamation in 1863. This effort culminated in the U.S. Congress adding the Thirteenth Amendment to the U.S. Constitution in 1865. The policy to abolish slavery gave rise to human rights protections for enslaved individuals, especially those working in the southern states.